Probiotic Community of Dage Banyumas: Next Generation Sequencing Approach - Eshananda, Yuriza; Fadlilah, Synta; Fikriyya, Nabela; Fitrianto, Nur; Kusumaningrum, Hermin (Biosaintifika: Journal of Biology & Biology Education, 2025)
Tempeh is known as a traditional fermented food that has been popular in Indonesia for hundreds of years. One of the tempeh that is widely consumed in Banyumas regency is Dage, which is made from fermented coconut waste. Currently, there is no information regarding the presence of probiotics in Dage. Therefore, this study aims to detect the diversity of probiotic types in the Dage tempeh microbiome using the Next Generation Sequencing (NGS) approach. The research stages consisted of sampling, enrichment in MRSB and R2A media, DNA extraction, Polymerase Chain Reaction (PCR), Illumina NGS-based sequencing, and bioinformatics analysis using QIIME2 and MEGA XI software. The results showed that the Dage was dominated by bacteria from the genera Lactobacillus, Weisella, and Acetobacter, which are known as a group of probiotics. In addition, bacteria from the genus Bifidobacterium and Enterococcus were also detected. Diversity analysis showed that Dage enriched in R2A medium had higher species diversity than in MRSB medium. However, the presence of the probiotic bacteria group was more abundant in MRSB medium. The dominant amplicons by phylogenetic analysis were identified as Lactobacillus spicheri, Lactobacillus zymae, Lactobacillus crustorum, Companilactobacillus farciminis, Weisella paramesenteroides, and Acetobacter indonesianensis, which previously have several probiotic properties. These results provide novel information regarding the presence of probiotic bacteria in Dage, which can be explored further using a culturable approach.